A new species of Corcyrogobius (Teleostei: Gobiidae) from Île de Ngor, Senegal - Kovačić, Marcelo; Wirtz, Peter; Schliewen, Ulrich K. (Zootaxa, 2020)
Corcyrogobius pulcher sp. nov. is described from off Île de Ngor, Dakar, Senegal. Corcyrogobius pulcher is distinguished from its two congeners by having the rear edge of the jaws ending posteriorly below mideye, second dorsal fin I/9, pectoral fin rays 17, pelvic fins oval or truncated posteriorly, scales in lateral series 26–27, anterior oculoscapular head canal with pore β, suborbital row b of sensory papillae anteriorly beginning below vertical of posterior edge of eye, dark vertical caudal bar, branchiostegal membrane without intense dark spot, cheek with two oblique whitish stripes, the first going from the eye downwards and forward to the posterior jaws, the second on the preopercular, alternating with brown oblique stripe going from behind the eye downwards and forward across the cheek. Furthermore, mitochondrial COI-barcoding data unambiguously support the species-level distinctiveness of the three Corcyrogobius species. A key to the species of Corcyrogobius is provided.